The applicability of an integrated clinical approach in the management of a patient with chronic aspecific coccygodynia in association with chronic aspecific low back pain: A case report. - Vignoni, Michele (Journal of Biomedical Practitioners, 2022)
INTRODUCTION Coccygodynia is a musculoskeletal disorder that reduces the quality of life of people in which it occurs. It affects about 1% of the general population with musculoskeletal disorders and it could be due to a multifactorial aetiology. Musculoskeletal disorders in other adjacent areas such as the sacroiliac and/or lumbo-sacral joints may also be associated in the physical examination. The current evidence for the diagnosis of coccygodynia is controversial both for the difficulty in the correlation between pain and structural factors and for the absence of evidence regarding the sensitivity and specificity of the clinical examination. Conservative treatment involves a series of passive interventions to reduce pain. The aim of this paper is to demonstrate how an integrated clinical reasoning could be used in the management of a patient with an aspecific musculoskeletal coccygodynia. CASE PRESENTATION The patient reports pain localized in the coccyx for about 3 years with worsening after activities in which there is an increase in load and/or long periods in standing position and/or when getting up from a prolonged sitting/supine position. The patient also refers pain in the lumbar spine. Both coccyx and lumbar pain decrease due to a partial limitation of daily life activities and an abstention from amateur football play. At physical examination the patient presents lumbar hyper-lordosis and hyper-activation of peri-vertebral muscles (static observation) with an alteration in lumbo-pelvic rhythm and during squat (dynamic observation). The palpation of the coccyx and the area adjacent to it causes coccygeal pain and refers to the sacroiliac joints. The functional diagnosis is ‘Chronic Aspecific Coccygodynia associated with Chronic Aspecific Low Back Pain’. A central mechanism of pain is prevalent in the maintenance of both musculoskeletal disorders. The reduction of functional and psychological impairments through desensitization, education and gradual increase in load is the tool of the treatment plan for a complete return to activity and participation. After five sessions the patient partially returns to daily life activities without any previously reported pain. At the follow-up at three, six, nine and twelve months there is a complete return to daily life activities and to playing football in the absence of coccygeal and lumbar pain. CONCLUSIONS This case report describes the success of pain functional and psychological management in a patient with ‘Chronic Aspecific Coccygodynia associated with Chronic Aspecific Low Back Pain’. The use of an integrated clinical approach in patients with coccygodynia could be a practical example to guide physiotherapists performing a functional diagnosis triage and to choose the correct treatment plan for each individual patient. Future studies could consider this decision-making process to validate it when a patient complains pain in the coccyx.